Between Sport and Leisure: Competitive Senior Ballroom Dancing as Serious Leisure - Finkielsztein, Mariusz (Qualitative Sociology Review, 2023)
The article examines the motivations, attitudes, and practices of senior ballroom dancing (dancers over 30 years of age). The paper is based on qualitative research (interviews and participant observation) conducted in one Warsaw dancing club and presents senior ballroom dancing as serious leisure as conceptualized by Robert Stebbins, that is, a pursuit of leisure activity that involves long-term commitment and substantial investment in one’s development (and thus, significant personal effort) that creates a distinct social world and a strong identification with the chosen activity. Dancing as a serious leisure activity falls somewhere in the middle of the sport-leisure continuum, and senior ballroom dancing is analyzed as a liminal case between these two, oscillating between recreation and competitive approach. The article investigates the process of professionalization of leisure, showing what place dance and competitions occupy in the lives of senior dancers.